THE DICHOTOMY OF THE ENEMY IMAGE IN THE MILITARY LITERATURE OF SHUKHRAT AND Y.BONDAREV (CANADA - SCIENTIFIC REVIEW OF THE PROBLEMS AND PROSPECTS OF MODERN SCIENCE AND EDUCATION, 2025)
Analysis of the enemy image in Shukhrat’s “Years in overcoats” and Yuri Bondarev’s “Hot snow” reveals the profound duality of this concept, which goes beyond mere military-strategic or ideological opposition. Considering the enemy simultaneously as a military and ideological antagonist enriches the dramaturgy of the texts, introducing philosophical and ethical dimensions. Both authors, despite differences in their approaches and contexts, converge in their desire to portray the enemy not as an abstract evil, but as a collection of living people, each possessing their own inner world, fears, and moral choices. Shukhrat’s use of Uzbek folk motifs and Bondarev’s detailed study of character psychology serve as powerful means for reflections on morality, ethics, and humanity in war, making the image of the enemy a key to understanding the deep moral dilemmas inherent in human nature.